Endophytic Fungi Producing Indole Acetic Acid from Melastoma malabathricum L. and Rhodomyrtus tomentosa (Aiton) Hassk. In Indonesia (Jurnal Online Pertanian Tropik, 2020)
Melastoma and Rhodomyrtus are known to have widespread distribution and considered as medicinal plants in Indonesia. However, information about the diversity of endophytic fungi in Melastoma malabathricum (MM) and Rhodomyrtus tomentosa (RT) is limited and their potential as an alternative source of indole acetic acid (IAA) has never been reported before. The purpose of this study was to determine the diversity of endophytic fungi from MM and RT which have the potential as an alternative source of IAA and potentially induce the germination of Capsicum annuum L. seeds. The research consisted of isolation of endophytic fungi, IAA production analysis, and capsicum seed germination test. Samples of MM and RT were obtained from Kelubi, East Belitung, Indonesia on August 7th, 2017. Endophytic fungi were isolated from various organs including : leaves, roots, stems, flowers, and fruits using surface sterilization method on the Malt Extract Agar (MEA). After purification, a total of 33 fungi were obtained (15 isolates from MM and 18 isolates from RT). Each endophytic colony shows unique and varied colony on a PDA medium. 17 endophytic fungal isolates in this study tested positive for IAA production. All strains produced different levels of IAA, where MIVA2, MIVD1, and MIVA3 had the highest levels of IAA concentrations (89 ppm, 82 ppm, and 70 ppm respectively). In the term of germination, there were 5 isolates which have high potential in inducing Capsicum annuum L. seeds, namely; MIVA3, MIVF3, RIVD2, RIVD5, RIVD6, RIVD9 (90%, 95%, 100%, 90%, 100%, 90%, respectively).